2009
DOI: 10.1111/j.1600-065x.2009.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory and coinhibitory receptors in anti‐tumor immunity

Abstract: Summary Despite the expression of antigens by tumor cells, spontaneous immune-mediated rejection of cancer seems to be a rare event. T-cell receptor engagement by peptide/major histocompatibility complexes constitutes the main signal for the activation of naive T cells but is not sufficient to initiate a productive generation and maintenance of effector cells. Full activation of T cells requires additional signals driven by costimulatory molecules present on activated antigen-presenting cells but rarely on tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
209
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(213 citation statements)
references
References 210 publications
1
209
2
1
Order By: Relevance
“…The expression and functional relevance of members of the B7 costimulatory family in tumor lesions of distinct histology have been frequently reported (13,17). Limited data are available for melanoma and in particular, the expression and significance of B7-H3 and B7-H4 molecules have not yet been analyzed in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression and functional relevance of members of the B7 costimulatory family in tumor lesions of distinct histology have been frequently reported (13,17). Limited data are available for melanoma and in particular, the expression and significance of B7-H3 and B7-H4 molecules have not yet been analyzed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…11). Even though many studies have shown an inhibitory role for B7-H4 (13) in the setting of progressive renal disease, a costimulatory activity of B7-H4 has also been proposed (14). So far, the receptor for B7-H4 has not been identified (12).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-documented in the recent decade that various tumors were able to exert immunogenic properties inducing strong anti-tumor immune reactions, in which T cells were shown to play a key role [1][2][3]. Numerous publications revealed a strong correlation between an infiltration of tumor lesions in cancer patients with T lymphocytes and better clinical outcome [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple regulatory mechanisms that blunt T cell function within the tumor microenvironment arise in tumors (27). Programmed death ligand 1 (PD-L1), an inhibitory molecule frequently upregulated on tumor cells, is one of the major immunological checkpoints contributing to tumor-immune escape (28) through the inhibition of T cell activation and promotion of apoptosis of DCs (29) and CD8 + T cells (30). In several clinical trials, blockade of programmed death-1 (PD-1) or PD-L1 resulted in enhanced T cell function and improved immune-mediated tumor control (31).…”
mentioning
confidence: 99%